Crowding phenomenon in breast cancer as a prognostic factor - N. V. Krakhmal; M. V. Zavyalova; S. V. Vtorushin; L. A. Tashireva; V. M. Perelmuter (Сибирский онкологический журнал, 2023)
Purpose: to evaluate the crowding-induced morphological changes in invasive breast carcinoma and compare the data obtained with the parameters of the tumor progression. Material and Methods. The study group included 107 patients (mean age: 57.2 ± 11.2 years) who did not receive neoadjuvant chemotherapy. Breast cancer morphological and immunohistochemical images were studied. The histological type of breast cancer was determined according to WHO recommendations (The WHO Classification of Breast Tumors, 5th Edition, 2019). The study included only cases with invasive breast carcinoma of no specific type. Clinical parameters were assessed using the patients' medical history. Statistical analysis was carried out using the Statistica 10.0 program. A p-value of 0.05 or lower was considered statistically significant. Results. The phenomenon of crowding in breast cancer was shown to be associated with lymph node metastases, with intratumoral heterogeneity of particular importance. The phenomenon of crowding was morphologically confirmed in all cases (n=40) with lymph node metastases in solid tumors. In these solid tumor structures, a decrease in the expression level of the proliferative index Ki67 was observed. In tumor sites with the evidence of crowding phenomenon in solid structures with lymph node metastasis, positive expression of integrin β1 was less frequently observed. Conclusion. Te results obtained suggest that the mechanism that initiates the process of tumor cell invasion may be based on crowding and basal cell extrusion, while the patterns found are a manifestation of changes in cell properties with the acquisition of a higher potential for mobility and cell migration.